Behavioral disinhibition and antiepileptic treatment in childhood epilepsy: A retrospective cohort study. Issue 1 (18th January 2017) - van Tuijl, Diana C.; Groenwold, Rolf H. H.; Vlaskamp, Chantal; van Campen, Jolien S.; Braun, Kees P. J.; Jansen, Floor E.; Bruining, Hilgo
Summary: Objective: To test whether specific classes of antiepileptic drugs increase the risk for behavioral disinhibition, a frequent complication of treatment of childhood epilepsy. Methods: In a sample of children with active epilepsy and antiepileptic drug (AED) treatment (n = 146, age 4–17 years), we performed a retrospective chart analysis of the occurrence of symptoms indicating reduced behavioral disinhibition following AED treatment. We used a risk‐set approach to analyze whether the presence or recent addition of AED categories defined by their mechanism of action were associated with enhanced risk for behavioral disinhibition symptoms. Results: Mean duration of follow‐up was 2, 343 days (range 218–6, 292, standard deviation [SD] 1, 437). Episodes of behavioral disinhibition were reported in 51 (34.9%) children, with variable latencies between latest change and occurrence of behavioral disinhibition symptoms (mean 67 days, range 2–367). Current use of AEDs targeting gamma‐aminobutyric acid (GABA) (odds ratio [OR] 1.8, 95% confidence interval [CI] 1.02–3.29, p = 0.04) and SV2A‐mediated neurotransmitter release (SV2A)‐mediated (2.0, 1.13–3.60, p = 0.02) neurotransmitter release was associated with increased risk for behavioral disinhibition. Restricting the analysis to the 90 days before behavioral disinhibition episode occurrence revealed that only addition of GABAergic AEDs (OR = 26.88, 95% CI = 6.71–107.76, p < 0.001) was associated with behavioral disinhibition. In contrast to our expectations, seizure control was reported to have improved parallel to most behavioral disinhibition episodes. Significance: This exploration of behavioral disinhibition in relation to antiepileptic drug treatment indicates that GABA potentiating drugs are specifically associated with behavioral problems during treatment of childhood epilepsy. Behavioral disinhibition episodes often occurred while seizure control improved, which may have reduced alertness for the consequences of AEDs on interictal symptoms. Our findings may be related to the increasing evidence for a role for excitatory actions of GABA in childhood epilepsy.